STRATEGI DALAM PENANGANAN KASUS LUMPUR LAPINDO PADA MASYARAKAT TERDAMPAK LUMPUR LAPINDO PORONG-SIDOARJO JAWA TIMUR - Dhesta Mey Intakhiya; Ulfah Primurdiani Santoso; Dyah Mutiarin (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2021)
This article discusses the strategic efforts in handling the Lapindo mudflow case and the impact caused by the community victims of the Lapindo mudflow case that occurred in Porong Sidoarjo, East Java. The government has tried to make various efforts to repair and rebuild assets to meet the needs of the victims of the Lapindo mudflow. The Lapindo mud disaster caused a huge impact in changing the social order, from the social system, social structure, to the economy and so on. This study uses a qualitative approach with case study methods and the data obtained are secondary data in the form of archives, photos, documents, literature, written sources, and so on. Then the NVivo application is also used which can answer the needs of qualitative researchers and the methods used are qualitative and quantitative in managing and analyzing data effectively and efficiently. The strategy for handling the victims of the Lapindo mudflow is still not good in terms of social, economic and other aspects because there is no handling from the government that supports the needs in terms of substituting livelihoods and other assistance for victims of the Lapindo mudflow, as well as the problem of compensation provided and not in accordance with the agreement at the beginning and there is a delay in payment